Language and Ecology In Silau Malela Society (Ecolinguistics Study) - Akmal akmal; Dwi Widayati (Fakultas Bahasa dan Budaya Asing (FBBA), Universitas Muhammadiyah Semarang, 2021)
This study focused on to ecolinguistics study that talks about the language and ecology in the Silau Malela society. This study was to find out how the people who lived in Silau Malela, merged into the environment to keep the balance between human and their environment. Ecolinguistics is an interdisciplinary study between ecology or environment and language (linguistics) which is expressed by the human. So this study was not focused on ecology, but it discussed language in life. This study used qualitative research by doing observation and interviewing the people who lived in Silau Malela. This research describes the relationship between human and environmental communication. This society is so familiar with their environment and they also keep the situation so that they can communicate to the surroundings such as their cows, dogs, and others (the pets) and plantations when they do their activities with their pets and plantation. They also gave the name for their pets and sometimes to their plantation so that they understood the meaning of their owner when they were talking to their environment.